Economic rewards in academia: analysis of empirical literature on merit pay in universities in seven countries - Bonifaz Chirinos, Mónica Patricia (2018)
The article presents a selective review of the literature that exposes and analyzes the results of ten empirical studies on the consequences of the application of economic incentives in academia in a context of global transformation of the university. The first part presents a brief description of incentive systems known as merit pay plans, their main characteristics and the objectives of their implementation. The second part presents the main research findings developed in the USA, Germany, Australia, Estonia, Pakistan, Argentina and Mexico, and the reported effects on productivity, motivation and teacher satisfaction. Concludes with the discussion of critical aspects in the implementation and evaluation of merit-based payment systems.